The artless Jew : medieval and modern affirmations and denials of the visual - Bland, Kalman P., 1942- (Princeton, NJ : Princeton University Press, 2000)
Conventional wisdom holds that Judaism is indifferent or even suspiciously hostile to the visual arts due to the Second Commandment's prohibition on creating "graven images," the dictates of monotheism, and historical happenstance. This intellectual history of medieval and modern Jewish attitudes toward art and representation overturns the modern assumption of Jewish iconophobia that denies to Jewish culture a visual dimension. Kalman Bland synthesizes evidence from medieval Jewish philosophy, mysticism, poetry, biblical commentaries, travelogues, and law, concluding that premodern Jewish intel.
Book Cover; Title; Copyright; Contents.
Includes bibliographical references (pages 201-228) and index.
Print version record.
Master record variable field(s) change: 082, 650
Keywords: Ten commandments -- Images; Ten commandments -- Images; Judaism and art -- History of doctrines; Jewish art; Jewish aesthetics; Jews -- Intellectual life; RELIGION -- Judaism -- Rituals & Practice; RELIGION -- Judaism -- History; Beeldende kunsten; Visualisatie; Esthetica; Jodendom; Electronic books